(untitled) (Asian Journal of Medical and Biological Research, 2015)
The objectives were to investigate the factors (age, sex, breed and season) affecting the occurrence of calf diseases. In this study 497 cases of 0 to 3 months of age from three different farms were investigated. Calf in Savar Dairy farm (n=249), Talbag Dairy Farm (n=85) and BAU Dairy Farm (n=163) were included from April 2011 to March 2012. The occurrence of diseases were classified on the basis of breed (Local and Cross), age (? 3 weeks and >3 weeks), sex (Male and Female) and season (Spring, Summer, Rainy and Winter). The overall diseases were diarrhoea (20.3%), anorexia (9.7%), fever (9.1%), naval ill (8.0%), malnutrition (7.7%), indigestion (6.7%), traumatic injury (5.4%), dysentery (5.0%), myiasis (4.6%), pneumonia (3.4%), alopecia (3.4%), atresia ani (3.2%), hernia (2.8%), constipation (2.6%), abscess (2.2%), conjunctivitis (2.2%), lameness (1.8%), FMD (1.2%) and blot (0.6%). The cases of diarrhoea was higher (20.5%) than that of other diseases. The occurrence of diseases was highly significant (p<0.01) in crossbred calves (77.3%) than that of local bred (22.7%). Cases of diseases were higher in male calves (51.7%) than that of female calves (48.3%) but the variation was insignificant (p>0.05). The effect of breeds on diseases were found significantly (p<0.05) higher in ? 3 weeks (55.1%) than that of > 3 weeks of age (44.9%). The occurrence of diseases in calves was significantly (p<0.05) higher in rainy season (36.0%) followed by the summer (31.0%), winter (22.1%) and lowest in spring (10.9%). The results demonstrate significant effect of breed, age and season on the occurrence of diseases in calves. Asian J. Med. Biol. Res. June 2015, 1(1): 39-46